Directed influence on anaerobic energy supply systems of qualified free style wrestlers - Sybil, M. G.; Pervachuk, R. V.; Chuiev, A. U. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to experimentally prove effectiveness of directed influence on anaerobic energy supply systems of free style wrestlers, considering individual characteristics of their bio energetic.